2021
DOI: 10.3390/ijms22031410
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of N-Substituted 3,4-Pyrroledicarboximides as Potential Anti-Inflammatory Agents

Abstract: In the present paper, we describe the biological activity of the newly designed and synthesized series N-substituted 3,4-pyrroledicarboximides 2a–2p. The compounds 2a–2p were obtained in good yields by one-pot, three-component condensation of pyrrolo[3,4-c]pyrrole scaffold (1a–c) with secondary amines and an excess of formaldehyde solution in C2H5OH. The structural properties of the compounds were characterized by 1H NMR, 13C NMR FT-IR, MS, and elemental analysis. Moreover, single crystal X-ray diffraction has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…Redzicka et al. 84 designed and synthesised a series of N-substituted 3,4-pyrroledicarboximides. All compounds exhibited stronger inhibition of COX-2 than the reference drug (meloxicam) and compounds 69a and 69b ( Figure 10 ) were proven to be the most effective against COX-2 enzyme.…”
Section: Recent Development In Anti-inflammatory Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Redzicka et al. 84 designed and synthesised a series of N-substituted 3,4-pyrroledicarboximides. All compounds exhibited stronger inhibition of COX-2 than the reference drug (meloxicam) and compounds 69a and 69b ( Figure 10 ) were proven to be the most effective against COX-2 enzyme.…”
Section: Recent Development In Anti-inflammatory Agentsmentioning
confidence: 99%
“…Replacement of aryl substituent in a series of piperazine derivatives with heteroaryl or cycloalkyl substitutes led to a significant reduction in COX-1 inhibition. Moreover, introduction of hydrophilic hydroxyethyl substitutes led to a decrease in the inhibitory activity in relation to both enzymes, while introduction of an OH group in a series of arylpiperidine derivatives significantly reduced COX-1 inhibition 84 .…”
Section: Recent Development In Anti-inflammatory Agentsmentioning
confidence: 99%
“…More recently, Redzicka et al [ 136 ] reported design, synthesis, and anti-inflammatory activity of N-substituted 3,4-pyrroledicarboximides (65 a–k), (66) and (67 a–d) ( Fig. 19 ) .…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…Triazoles have been shown to have confirmed eligible characteristics, like reduction conditions, high acid-base hydrolysis stability and metabolic degradation-resistance [8,9]. They include electrical, mechanical, magnetic, optical and corrosion properties far better than their individual components, because of their electroactive and conductive nature [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%